Secular change of tectonic setting in the Archean Takanen greenstone belt, northeastern Karelia Province, Fennoscandian Shield - Ville Järvinen; Nikolaos Karampelas; Tapani Rämö; Tapio Halkoaho; Tuomo Törmänen; Perttu Mikkola; Yann Lahaye (Bulletin of the Geological Society of Finland, 2023)
The target of this study is the Takanen greenstone belt (TGB), a small 11-km-long and east-west oriented supracrustal belt in the northern Lentua complex of the Western Karelia Subprovince (eastern Finland). We present a new geological interpretation of the TGB based on lithology, geochemistry, stratigraphy, and two new zircon U-Pb age determinations and Lu-Hf-in-zircon data. The TGB forms a ≥800-m-thick synclinal sequence composed of intercalated mafic-komatiitic and felsic-intermediate volcanic and volcaniclastic rocks (lavas, tuffs, and tuffites) crosscut by granitoid dykes, and metamorphosed in lower amphibolite facies with few primary volcanic textures visible. The felsic-intermediate rocks are calc-alkaline and split into strongly and weakly REE-fractionated groups. The mafic-ultramafic rocks are tholeiitic with flat REE-patterns, but some samples show LREE-enrichment. Massive Fe-sulfide layers (≤1 m) are associated with volcaniclastic rocks. Komatiites are Al-undepleted and comprise differentiated (peridotite-gabbro) and undifferentiated (dunite/serpentinite) cumulates and thin undifferentiated flows. Channel-facies komatiitic cumulates are found stratigraphically above Fe-sulfide-rich units and have potential for komatiite-hosted Ni-deposits. Our new isotope data from two felsic-intermediate volcanic rock samples shows that the TGBs stratigraphically lowermost and uppermost units are 2.96 Ga and 2.71 Ga old, respectively. Based on Hf isotope data, the older 2.96 Ga sample contains reworked crustal material, possibly originating from ~3.2 Ga crust. In contrast, the 2.71 Ga sample is isotopically juvenile (near-chondritic), indicating an episode of juvenile crust formation in the northern Lentua Complex. No unconformity is found between the stratigraphically upper and lower parts of the TGB, but the ~250 Ma age difference (and geochemical indicators) suggests they may have formed in different tectonic settings. The lower part of TGB stratigraphy is correlated with the ~2.94 Ga Luoma Formation in the nearby Suomussalmi greenstone belt. The 2.71 Ga volcanic unit does not have a known equivalent in greenstone belts in Finland, but a corollary is found in Russia, and a tentative correlation to a possible 2.75–2.70 Ga arc-system in Takanen–Khedozero-Bolshozero–Ilomantsi is suggested.